Responsabilidade civil ambiental como instrumento de efetividade do direito fundamental ao ambiente ecologicamente equilibrado - Fochi, Helena Raab (2012)
The present work aims at studying the fundamental right to a balanced environment, analyzed from the perspective of the institution of civil liability. Indeed, the evolution of environmental issues is denoted, from the concern triggered between the 60s and 70s through discussions initiated by the environmental movements, it started receiving protection by the legal science, as a constitutionalized right included in the list of fundamental rights in several countries. What is more, with nuances highlighted in the sphere of the Principle of Human Dignity. However, to ensure environmental protection it is necessary not only constitutional guarantors of fundamental rights but also liability regime with very clear deterrent function. Also, it is necessary to exalt the solidarity between current and future generations and the intersection between the spheres of Public and Private Law, for the greater purpose of effectiveness and implementation of the right to healthy and balanced environment to the whole community.